Queer Musings on Masculinity and History - Maynard, Steven (Labour / Le Travail, 1998)
Commentates on the satirical piece, "To the Dartmouth Station" (1976), and the author's article, "Rough Work and Rugged Men" (1989), both of which were published in the journal, in order to raise questions regarding the historical study of working-class masculinity. Argues for greater use of the analytical lens of sexuality to interrogate the concept of masculinity, including that masculinity is in crisis, and to explore workingmen's gender identities and sexual practices. Considers issues of sexuality and indications of homosexual subcultures in historically male occupations such as seafaring, lumbering and mining. Concludes that the investigation of how men's sexual and gender relations existed in relationship to other forms of power highlights the potential of gay history to both complicate and expand historical understandings of working-class men's gender identities.

Sex, Court Records, and Labour History - Maynard, Steven (Labour / Le Travail, 1994)
Examines crown attorney prosecution files at the Archives of Ontario as primary source material on communism in Canada, union organizing, strike activity, state surveillance, the role of women and youth in left-wing politics and the labour movement, and gender and sexual relations in labour organizing. Discusses several court cases and reproduces a 1929 Communist Party leaflet used as evidence in charging four women with circulating seditious pamphlets. Concludes that the evidence in the files sheds light on the collective struggle for economic and social justice for working people.
Keywords: COMMUNIST parties; Canada; Communists; Court records; Labor movement; Political activity; STRIKES & lockouts -- History; WOMEN communists

Passion and Power: Sexuality in History - Maynard, Steven (Labour / Le Travail, 1991)
The article reviews the book, "Passion and Power: Sexuality in History," edited by Kathy Peiss and Christina Simmons.
Keywords: BOOKS -- Reviews; HUMAN sexuality & history; Nonfiction; PASSION & Power: Sexuality in History (Book); PEISS, Kathy; SIMMONS, Christina

Rough Work and Rugged Men: The Social Construction of Masculinity in Working-Class History - Maynard, Steven (Labour / Le Travail, 1989)
This paper uses two recent books in Canadian labour history, Craig Heron's "Working in Steel" and Ian Radforth's "Bushworkers and Bosses," to briefly review the place of masculinity in working-class history. The author suggests that while Heron and Radforth introduce masculinity into their studies, they do not fully develop all of its meanings and functions. Drawing upon the literature on the social construction of work, gender, and sexuality, the paper then goes on to suggest some ways in which we can begin to explore aspects of masculinity and sexuality within working-class history.
Keywords: EMPLOYMENT (Economic theory); HUMAN sexuality -- Psychological aspects; LABOR market; LABOR supply; Masculinity; SOCIAL constructionism

The Regulation of Desire: Sexuality in Canada - Maynard, Steven (Labour / Le Travail, 1989)
The article reviews the book, "The Regulation of Desire: Sexuality in Canada," by Gary Kinsman.
Keywords: Gender; KINSMAN, Gary; Nonfiction; REGULATION of Desire: Sexuality in Canada (Book); REVIEWS; books